Development of an Anchoring System for the Soft Asteroid Landing Exploration - Zhijun Zhao; Shuang Wang; Delun Li; Hongtao Wang; Yongbing Wang; Jingdong Zhao (International Journal of Aerospace Engineering)
The landing mechanism is easy to flow away from the surface of the asteroid, as there is nearly no gravity on the asteroid. One of the most problems for the asteroid landing exploration is to anchor the landing mechanism on the asteroid surface. In the paper, an anchoring system employed on the soft asteroid anchoring is designed. It is mainly composed of penetrating unit, advancing unit, winding unit, damping unit, and so on. On the basis of the mechanical design, the resistance characteristic of the anchor body in penetrating process is analyzed, and the shape of the anchor tip is designed with the least resistance as the constraint. Then, the validity of the anchor tip design is tested by comparing penetrating ability of different anchor tips. Finally, the penetrating and the anchoring performances of the anchoring system are tested in a variety of media.